2015
DOI: 10.1002/jbm.a.35421
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of intracellular detection of glucose through nonenzymatic and boronic acid functionalized carbon dots

Abstract: The objective of the research described here is to elucidate the fundamental mechanism by which the new class of "inert" non-enzymatic and boronic acid functionalized carbon dots-based sensors facilitate intracellular detection of glucose. The study suggests that the mechanism of detection of glucose involved selective assembly and fluorescence quenching of the carbon dots with excellent dynamic response to varying concentration of glucose within the biological range (1-100 mM). The strong dynamic response was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…In vivo bioimaging and biosensing based on functionalized C-dots was investigated by various researchers. 10,14,16,22,23,25,167,168,176,178,188,[198][199][200][201][202][203][204][205][206][207][208][209][210] The first work on C-dots for bioimaging applications was reported by the Sun group. 167 In this paper, the authors synthesized PEG 1500Npassivated C-dots via laser ablation and passivation.…”
Section: Bioapplicationmentioning
confidence: 99%
“…In vivo bioimaging and biosensing based on functionalized C-dots was investigated by various researchers. 10,14,16,22,23,25,167,168,176,178,188,[198][199][200][201][202][203][204][205][206][207][208][209][210] The first work on C-dots for bioimaging applications was reported by the Sun group. 167 In this paper, the authors synthesized PEG 1500Npassivated C-dots via laser ablation and passivation.…”
Section: Bioapplicationmentioning
confidence: 99%
“…In addition to that, the authors found that the presence of sulfide anions can recover the fluorescence of the quenched CNDs, leading to the development of an "off-on" system. Intracellular glucose was the target of the aminophenyl boronic acid-functionalized CNDs that Kiran et al developed [84]. The higher the concentration of the intracellular glucose the lower the intensity of the fluorescence emitted.…”
Section: Target-specific Imaging Applications For Eukaryotic Cellsmentioning
confidence: 99%
“…On the other hand, they may cause the mediated signaling cascade. Moreover, nanoparticles may potentially act like enzyme in many biological chemical reactions, named as nanozyme, though whether C‐dots also have the nanozyme‐inhibitor activity is unclear. Herein, we tested the function of C‐dots in peroxidase activity with pH‐mediated regulation and their potential to react with reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%